2000
DOI: 10.1016/s0921-4534(00)00406-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic inhomogeneity and the origin of the pseudogap

Abstract: Properties of manganites are greatly affected by cooperative Jahn-Teller effect and Hund's interaction. The insulating (undoped) as well as metallic ferromagnetic states can be described from a unified point of view based on two-band picture. The system is intrinsically inhomogeneous and the metal-insulator transition is treated by means of percolation theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Recently it has been shown that for QCP models this relation will lead to (T DW (x)/T max DW ) 2 + (T c (x)/T max c ) 2 = 1 [114]. Many other possible reasons for pseudogap formation have been suggested, such as, for example, an intrinsic inhomogeneity [115], d-wave-type Fermi surface deformations (Pomeranchuk instability) [116], or interaction with diatomic negative U centers [117], but it is hardly possible even to mention all of them here.…”
Section: Theories Of Pseudogapmentioning
confidence: 99%
“…Recently it has been shown that for QCP models this relation will lead to (T DW (x)/T max DW ) 2 + (T c (x)/T max c ) 2 = 1 [114]. Many other possible reasons for pseudogap formation have been suggested, such as, for example, an intrinsic inhomogeneity [115], d-wave-type Fermi surface deformations (Pomeranchuk instability) [116], or interaction with diatomic negative U centers [117], but it is hardly possible even to mention all of them here.…”
Section: Theories Of Pseudogapmentioning
confidence: 99%
“…The percolation of Sr 2 CuO 3 -type defects might explain the "granular metal" type conduction observed at higher temperatures in high resistivity samples. One might also be observing charge inhomogeneity as has been proposed for other cuprates [7]. However, this does not explain the metalinsulator transition that is observed in the Sr 1-x CuO 2-d films.…”
Section: Resultsmentioning
confidence: 87%
“…As was mentioned above, an inhomogeneity can be caused also by an inhomogeneous distribution of carriers (see Ovchinnikov et al (2000)). However, since the inhomogeneous distribution of pair-breakers (dopants) appears to be the dominant source of inhomogeneity ,we focus below (see Sec.…”
Section: Qualitative Picturementioning
confidence: 88%
“…Indeed, the pair-breaking effect in borocarbides as a major source of inhomogeneity (see Sec. II) was analyzed by Ovchinnikov and Kresin (2000). An unconventional temperature dependence of the critical fields Hc and Hc 2 observed experimentally (Schmiedeshoff et al, (2001)) was explained by the presence of pair-breakers.…”
Section: Itmentioning
confidence: 95%
See 1 more Smart Citation